Development and Use of Game-Based Instructional Materials for Teaching Science, Technology, and Society to College Students - Balic, Allan Gregy Villanueva; De Gracia, Rommel Selda (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study developed and evaluated game-based instructional ma-terials to enhance learning in the college-level subject, Science, Tech-nology, and Society (STS). Using an action research approach, the study addressed the limitations of traditional teaching methods by introducing the "ALLAN Star Card," inspired by Bingo, and the "Amaz-ing Challenge," modeled after the game show Who Wants to Be a Mil-lionaire. These tools were designed to promote student engagement, critical thinking, and active participation. The research included 30 first-year BS Agribusiness students from Bayambang Polytechnic Col-lege, selected through purposive sampling. Pre- and post-tests were administered to assess the effectiveness of the materials, alongside evaluations using the LRMDS Non-Print Instructional Materials Tool. The instructional materials received a "Very Satisfactory" rating, with an average content quality score of 3.81 (SD = 0.13). However, areas such as technical quality and user control required further improve-ment, particularly in minimizing technical issues and enhancing user interaction.Results from the pre-test (M=6.9, SD=2.81) and post-test (M=10.47, SD=3.31) revealed a significant improvement in student performance, confirming the efficacy of game-based methods in boosting academic achievement. These findings align with prior re-search on the advantages of gamification in education. Recommenda-tions for improvement include addressing grammatical errors, reduc-ing lifeline usage, and implementing time constraints for activities. The study concludes that game-based instructional materials effec-tively enhance learner engagement and academic performance in higher education.